Effect of aging on the microstructure, hardness and chemical composition of dentin (2023)
Objective Understanding the effects of biological aging on human tissues has been a topic of extensive research. With the increase in healthy seniors and quality of life that topic is becoming increasingly important. In this investigation the effects of aging on the microstructure, chemical composition and hardness of human coronal dentin was studied from a comparison of teeth within "young" and "old" age groups. Methods The microstructure of dentin within three regions (i.e., inner, middle and outer) was analyzed using electron and optical microscopy. The mineral-to-collagen ratio in these three regions was estimated using Raman spectroscopy and the hardness was evaluated using microindentation. Results Results showed that there were significant differences in tubule density, tubule diameter and peritubular cuff diameter with depth. Although there was no difference in tubule density and diameter of the tubules between the age groups, there was a significant difference in the occlusion ratio. A significant increase in hardness between young and old patients was found for middle and outer dentin. An increase in mineral-to-collagen ratio from inner to outer dentin was also found for both groups. In old patients, an increase in mineral content was found in outer coronal dentin as a consequence of tubule occlusion. Conclusions An increase in occlusion ratio, hardness, and mineral content was found in the dentin of adult patients with age. This increase is most evident in the outer coronal dentin. © 2015 Elsevier Ltd. All rights reserved.